A review on impact of leadership styles in organizations - Fatma Bozkurt; Afet Kıyak (Sakarya Üniversitesi İşletme Enstitüsü Dergisi)
This study aims to investigate the different effects of different leadership styles on the organization with a new projected discussion model and to prove that it produces varied outcomes. The study explains what leadership is, gives detailed information on major leadership styles and well-known theories, and discusses how gender differences and emotional intelligence relate to the leadership styles. The study builds on the broad existing literature reviews and arguments. The existing theoretical frameworks on different approaches of leadership styles and arguments are presented consistent with the view of leadership concept influence teamwork collaboration, cooperation, and organizational performance. Moreover, another aim of this study is to correct the false facts by explaining the differences between a leader and a manager and to support the theoretical gaps in these areas with different proven approaches. After reviewing and explaining the concept of leadership approaches and styles in organizational management strategies, the importance of behavioral and personal characteristics of leaders are emphasized. In this context, different variables (such as gender differences and emotional intelligence) are effective in shaping leadership styles. An argument is presented that a casual relationship exists between different variables and the leadership styles; the casual relationship is moderated by firm-varying selections of leadership types. Also, the research paper predicts how leadership will evolve in the future. The concept of leadership is changing with the widespread use of new high technologies and the speed of globalization. Therefore, organizations take this into account while determining their long-term goals. By the time, the impact of these goals on corporate culture is also modifying and transforming.